2011
DOI: 10.1063/1.3578472
|View full text |Cite
|
Sign up to set email alerts
|

Structural dynamics of supercooled water from quasielastic neutron scattering and molecular simulations

Abstract: One of the outstanding challenges presented by liquid water is to understand how molecules can move on a picosecond time scale despite being incorporated in a three-dimensional network of relatively strong H-bonds. This challenge is exacerbated in the supercooled state, where the dramatic slowing down of structural dynamics is reminiscent of the, equally poorly understood, generic behavior of liquids near the glass transition temperature. By probing single-molecule dynamics on a wide range of time and length s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

27
230
1
8

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 183 publications
(266 citation statements)
references
References 76 publications
27
230
1
8
Order By: Relevance
“…A review of supercooled water studies can be found in Debenedetti (2003). Typically, these experiments involve techniques such as nuclear magnetic resonance (Mallamace et al, 2006), quasielastic neutron scattering (Qvist et al, 2011), small angle X-ray diffraction (Huang et al, 2010), and others.…”
Section: Introductionmentioning
confidence: 99%
“…A review of supercooled water studies can be found in Debenedetti (2003). Typically, these experiments involve techniques such as nuclear magnetic resonance (Mallamace et al, 2006), quasielastic neutron scattering (Qvist et al, 2011), small angle X-ray diffraction (Huang et al, 2010), and others.…”
Section: Introductionmentioning
confidence: 99%
“…as the mass diffusion motions and vibrations 105 but provides a more accurate description of the low temperature regime with respect to the roto-translational model.…”
mentioning
confidence: 99%
“…This method, recently applied on high-quality QENS data 105 , leads to the identification of two highly entangled motional components, corresponding to two distinct types of structural dynamics:…”
mentioning
confidence: 99%
“…It has been previously reported by Krynicki et al [11] that the diffusion constant of bulk water at standard pressure and a temperature of 298.2 K is D = 2.30 × 10 −9 m 2 /s [11] in their paper utilizing the nuclear magnetic resonance spin echo technique. Teixeira et al and Qvist et al have published results from quasi-elastic incoherent neutron scattering from bulk water at a variety of temperatures where they found that two relaxation processes were associated with the quasi-elastic peak [12,13], which is how we have chosen to analyze our lateral diffusion data thus far. Qvist et al 's diffusion constants as a result of experiment and molecular simulations at 297.1 K are 2.16 × 10 −9 m 2 /s [13] and 2.20 × 10 −9 m 2 /s [13], respectively.…”
Section: -P2 Qens/wins 2014mentioning
confidence: 99%
“…Teixeira et al and Qvist et al have published results from quasi-elastic incoherent neutron scattering from bulk water at a variety of temperatures where they found that two relaxation processes were associated with the quasi-elastic peak [12,13], which is how we have chosen to analyze our lateral diffusion data thus far. Qvist et al 's diffusion constants as a result of experiment and molecular simulations at 297.1 K are 2.16 × 10 −9 m 2 /s [13] and 2.20 × 10 −9 m 2 /s [13], respectively. We can at this point not comment on the difference between our diffusion constants with respect to bulk water.…”
Section: -P2 Qens/wins 2014mentioning
confidence: 99%